Peroxisome Proliferator-Activated Receptor γ Induces the Expression of Tissue Factor Pathway Inhibitor-1 (TFPI-1) in Human Macrophages - G. Chinetti-Gbaguidi; C. Copin; B. Derudas; N. Marx; J. Eechkoute; B. Staels (PPAR Research, 2016)
Tissue factor (TF) is the initiator of the blood coagulation cascade after interaction with the activated factor VII (FVIIa). Moreover, the TF/FVIIa complex also activates intracellular signalling pathways leading to the production of inflammatory cytokines. The TF/FVIIa complex is inhibited by the tissue factor pathway inhibitor-1 (TFPI-1). Peroxisome proliferator-activated receptor gamma (PPARγ) is a transcription factor that, together with PPARα and PPARβ/δ, controls macrophage functions. However, whether PPARγ activation modulates the expression of TFP1-1 in human macrophages is not known. Here we report that PPARγ activation increases the expression of TFPI-1 in human macrophages in vitro as well as in vivo in circulating peripheral blood mononuclear cells. The induction of TFPI-1 expression by PPARγ ligands, an effect shared by the activation of PPARα and PPARβ/δ, occurs also in proinflammatory M1 and in anti-inflammatory M2 polarized macrophages. As a functional consequence, treatment with PPARγ ligands significantly reduces the inflammatory response induced by FVIIa, as measured by variations in the IL-8, MMP-2, and MCP-1 expression. These data identify a novel role for PPARγ in the control of TF the pathway.